The role of FFR in clinical decision making in patients with moderate coronary lesions: a pilot study - Safi, Morteza; Mehrabi, Mohammad Ali; Alipour Parsa, Saeed; Khaheshi, Isa; Naderian, Mohammadreza (Acta Biomedica Atenei Parmensis, 2018)
Background and Aim: Applying fractional flow reserve (FFR) recently helped to assess borderline coronary defects and also facilitates assessment of these lesions. The present study aimed to assess cost-effectiveness of FFR in detection of these borderline lesions. Methods: This cross-sectional study was conducted on140 consecutive patients with 219 diseased arteries who underwent coronary angiography and suffered intermediate coronary lesions. Results: Of 18 patients who candidate for CABG before FFR, only one patient underwent CABG after determining FFR (P-value<0.05), while 15 patients were scheduled for PCI and 2 patients for medical treatment. Of 122 patients who candidate for PCI, 59 were programmed to underwent PCI after FFR determination(P-value<0.05), while the strategy in 63 patients (47 with one-vessel disease, 15 with two vessel diseases, and 1 with three vessel diseases) was modified to medical treatment. Considering strategy modifying from PCI to medical treatment, 101 stents were saved (P-value<0.05). Also, in change of strategy from CABG to PCI, spending has decreased as much as 77.3% (P-value<0.05). Furthermore, the change of treatment approach from PCI on much number of coronary vessels to PCI on less number of coronary lesions led to saving of 52.2% of costs(P-value<0.05). Conclusions: In patients with an intermediate coronary lesion, measuring FFR to guide the decision to determine treatment strategy may lead to significant cost savings.